Development of USA method (understanding, sketching, analysing) as practical way to resolving classical mechanics problems for physics lesson - Rabiudin; Nurafifi, E H (Journal of physics. Conference series, 2021)
This study aims to develop a problem solving method known as the USA method (Understanding, Sketching and analysing) as a practical method to solving classical mechanics problems. This research method uses the ADDIE Research and Development model (Analysis, Design, Develop, Implementation and Evaluation) with data analysis techniques using Aiken’s validation and reliability analysis. Research subjects in several physics subject teachers and science class students in West of Papua with the research stages used Problem Analysis and learning needs, USA method design, method development, implementation and evaluation of method. Researchers used 21 validators consisting of 13 validators from physics and mathematics experts who teach at universities and 8 physics teacher participants as practitioners who teach in schools. The results of this development indicate that the level of validity of all assessment indicators reaches 0.75 to 0.928 with a reliability of 0.82 where this interval is called high validity and reliability. The final step is to apply the USA method and then analyse the effectiveness and practicality of this method. The important results obtained by the researcher were 92.5% of respondents stated that the USA method was effective as a better method to supporting the quality of learning physics in classical mechanics lessons. Meanwhile 94.3% of respondents said the USA method was practical as an easy way to understand classical mechanics.